2022
DOI: 10.3390/cells11152359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Inflammation in Sarcopenia: Diagnosis and Therapeutic Update

Abstract: Sarcopenia is generally an age-related condition that directly impacts the quality of life. It is also related to chronic diseases such as metabolic dysfunction associated with diabetes and obesity. This means that everyone will be vulnerable to sarcopenia at some point in their life. Research to find the precise molecular mechanisms implicated in this condition can increase knowledge for the better prevention, diagnosis, and treatment of sarcopenia. Our work gathered the most recent research regarding inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 155 publications
2
36
0
Order By: Relevance
“…Diabetic sarcopenia is an inevitable complication of T2DM, characterized by three major features, that is, decreased muscle mass, weakened muscle strength and reduced physical performance 1 . In our study, the diabetic mice demonstrated the above features, suggesting obvious sarcopenia.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Diabetic sarcopenia is an inevitable complication of T2DM, characterized by three major features, that is, decreased muscle mass, weakened muscle strength and reduced physical performance 1 . In our study, the diabetic mice demonstrated the above features, suggesting obvious sarcopenia.…”
Section: Discussionsupporting
confidence: 54%
“…Sarcopenia is a degenerative syndrome characterized by declined muscle mass, muscle strength and physical performance and leads to frailty, falls, physical disability and even mortality 1,2 . Diabetes mellitus (DM) has been reported as a common risk factor for sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis can cause inflammation that is activated by extracellular or intracellular stimuli [ 52 ] and is associated with various diseases, such as cardiovascular disease [ 53 ], Alzheimer’s disease [ 54 ], atherosclerosis [ 55 ], and muscle atrophy [ 56 ]. A recent study showed that pyroptosis occurs during dexamethasone-induced muscle atrophy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulation is also a relevant therapeutic approach for other pathological skeletal muscle conditions, such as sarcopenia, or the loss of muscle mass that occurs with age. Sarcopenia is associated with changes in the skeletal muscle microenvironment, such as an imbalanced inflammatory infiltrate and high levels of pro-inflammatory cytokines [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%